THE EFFECTIVENESS OF COGNITIVE-BEHAVIORAL THERAPY IN THE TREATMENT OF TOURETTE SYNDROME: A systematic review - Nunes Mesquita, Sabryna Hellen (2024)
This work addressed Tourette Syndrome (TS) as a complex challenge that affects not only the physical but also the psychological aspects of individuals. The history of the syndrome, the course of the disease, associated pathologies, and treatment options were explored. The objective of this review was established: to map studies addressing the importance of Cognitive-Behavioral Therapy (CBT) in the treatment of TS. Thus, the research was conducted in the database: Biblioteca Virtual de Saúde - BVS, where the descriptors used were: “Tourette Syndrome” AND “Cognitive-Behavioral Therapy”. This research resulted in a total of 76 articles, 74 of which were in English, from the periods 1985 to 2023. CBT was highlighted as a relevant therapeutic approach for TS, and its contributions and challenges were emphasized. The importance of addressing these issues to improve care and well-being of patients with TS was underscored. Topics such as symptom variation, long-term outcome assessment, contextual influences, and the integration of CBT with other therapeutic approaches were discussed. The study concluded by pointing out the scarcity of Brazilian research in the area and proposed a future direction for research, aiming to improve the quality of life of patients with TS through adapted CBT and greater contribution from psychology.